Allowance transactions in the EU ETS - Evidence from Austrian companies - Claudia Kettner; Daniela Kletzan-Slamanig (Austrian Institute of Economic Research (WIFO), 2022)
Emission trading has been the key instrument in the EU's climate policy since its introduction in 2005. According to economic literature, emissions trading should ensure the achievement of a given reduction target at the lowest possible costs, by equalising marginal abatement costs of the installations covered. According to previous studies, however, only a limited number of companies have engaged in trading pointing at a limited economic efficiency of the scheme. This paper contributes to the growing body of empirical literature on allowance transactions by providing an analysis for Austria. For this purpose, two approaches are combined - a quantitative analysis of data on allowance transactions from the EUTL and a survey among Austrian firms in the EU ETS on their trading behaviour, motivations, and strategies. Our results show that allowance transactions have increased over time and that Austrian companies in the EU ETS tend to mainly acquire allowances in the market. The majority of Austrian companies reported compliance as the main motive for purchasing allowances. However, they stated that the time horizon of buying allowances for compliance purposes has been rather short so far, but some Austrian ETS participants intend to emphasise earlier purchases and consider a longer period in their purchasing strategy. Moreover, our analysis shows that it is a limited number of large companies (trading companies and large energy suppliers) that is very active in the market. Market actors have gotten accustomed to this new market for emissions over the past 16 years which is illustrated by increasing quantities and volumes traded. Nevertheless, for Austrian companies there is some potential for adapting their trading strategies in order to incorporate the future challenges, primarily for those companies not used to trading on international energy or resource markets.
Keywords: 330; EU Emission Trading Scheme; Data analysis; Survey; Austria; Trading behaviour